Fast and flexible production of mechatronic integrated devices by means of additive manufacturing - Niese, Bernd; Amend, Philipp; Frick, Thomas; Roth, Stephan; Schmidt, Michael (2016 12th International Congress Molded Interconnect Devices - Scientific Proceedings, MID 2016, 2016)
Due to continuous improvements in process technology additively generated components are increasingly used for prototypes and small series devices. In comparison to conventional manufacturing process chain, additive manufacturing enables in principle embedding of conductive circuits and electronic components during the part building process. However, technologies like Selective Laser Sintering (SLS) or stereolithography (SLA) imply disadvantages concerning high process temperatures or time consuming cleaning steps. In contrast, Fused Deposition Modeling (FDM) seems to be well suited for production of mechatronic integrated devices due to the use of thermoplastic materials for electronic productions (e.g. ABS, PC/ABS), a low thermal load of electronic parts and a simple process management. In this paper, additive manufacturing of mechatronic devices by means of FDM in combination with direct printing of silver ink for generating conductive circuits is investigated. The silver ink is deposited in the matrix or applied on the surface of the part by a dispensing system during the building process. The in situ sintering process of the ink is carried out by a subsequently infrared laser (IR) irradiation. In order to generate components with a high mechanical stability the adhesion of the extruded material strings is optimized considering processing temperature and flow properties of the extruded thermoplastics (ABS, PC/ABS). Furthermore, depending on the flow behavior important FDM process parameters (e.g. volume flow, hatch distance) are adjusted to minimize cavities and generate media-tight components. The conductive circuits are characterized with respect to their electrical conductivity and mechanical stability.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Additive manufacturing; electrical conductive circuits; embedding; silver particle ink; sintering by laser radiation